Tannic Acid-Induced Surface-Catalyzed Secondary Nucleation during the Amyloid Fibrillation of Hen Egg-White Lysozyme - Tian, Jing (Int J Mol Sci, 2018)
Amyloid fibrillation by hen egg white lysozyme under the influence of tannic acid was investigated by atomic force microscopy and fluorescence spectroscopy. Tannic acid was found to be able to induce the formation of amyloid fibrils with an interesting mixed morphology. Such morphology features with the existence of areas of thickening alternating with areas of normal height. This novel modulation effect of tannic acid on amyloid fibrillation was interpreted by the established surface-catalyzed secondary nucleation theory. We further performed a fluorescence quenching study to investigate the intermolecular interaction between tannic acid and lysozyme. The results support that lysozyme and tannic acid interact with each other mainly through hydrophobic interactions. We also discussed why hydrogen-bonding interaction is not a dominant factor in the interaction between tannic acid and lysozyme though tannic acid contains a significant amount of hydroxyl groups. Our work provides new insight into the effect of tannic acid, a well-known amyloid inhibitor, on amyloid fibrillation.